The importance of incisional biopsy for diagnostic confirmation of aneurysmatic bone cyst: Case report (Research, Society and Development, 2023)
Aneurysmal bone cyst is a rare benign lesion, corresponding to 1% of bone cysts that present rapid, osteolytic and expansive growth, with greater occurrence in long bones and vertebrae. When related to facial bones, it has a greater predominance in the mandibular bone, in addition to having a small predilection for females. Its etiology differs among authors, and it is argued that its occurrence may be due to trauma, a preexisting injury or hemodynamic changes. It has radiographic characteristics in common with other lesions, presenting a uninucleate or multinucleate radiolucent image, septate radiopaque areas and well-defined margins, similar to injuries: Odontogenic Keratocyst, Ameloblastic Fibroma, Myxoma and others. Therefore, the objective of this case report was to present the importance of performing an incisional biopsy, in order to obtain a final oral diagnosis, since it would not be possible through imaging tests. For this, a partial removal of the lesion was carried out, in the anterior region of the mandible, of a female patient, P.N.S, leukoederma, 33 years old, undergoing hemodynamic treatment for 14 years, with subsequent referral of the material collected for histopathological analysis, which after verification of the fragments, there was the diagnostic confirmation of the Aneurysmal Bone Cyst, and better treatment and prognosis guidelines could be offered to the patient.